การจัดการกับความกลัวความเจ็บปวดจากการแทงเข็มในเด็ก : ปฏิบัติการพยาบาลในการดูแลผู้ป่วยเด็ก - ทรัพย์สังข์, อลิษา; ขุนแก้ว, เสน่ห์; อุดมเลิศ, มณฑา (Journal of The Royal Thai Army Nurses, 2017)
การแทงเข็มเป็นหัตถการที่พบได้มากในผู้ป่วยเด็กที่เข้ารับการรักษาในโรงพยาบาล และเป็นสาเหตุที่ทำให้ผู้ป่วยเด็กเกิดความกลัวเจ็บปวด ทำให้เด็กต่อต้านไม่ให้ความร่วมมือในการรักษา ดิ้น ขัดขืน ส่งผลกระทบต่อแผนการรักษา นอกจากนี้ยังก่อให้เกิดประสบการณ์ด้านลบต่อการเข้ารับการรักษาในโรงพยาบาลและบุคลากรทางการแพทย์ การจัดการกับความกลัวและความเจ็บปวดจึงเป็นสิ่งสำคัญที่เป็นบทบาทและหน้าที่โดยตรงของพยาบาลในการให้การดูแลผู้ป่วยเด็กและครอบครัว เพื่อช่วยให้เด็กรู้สึกปลอดภัย สามารถเผชิญ กับความกลัวและความเจ็บปวดได้อย่างเหมาะสม อันจะเป็นการตอบสนองความต้องการทางด้านจิตใจของผู้ป่วยเด็ก ทำให้เด็กสามารถก้าวเข้าสู่พัฒนาการในขั้นต่อไปได้อย่างสมบูรณ์ บทความนี้มีวัตถุประสงค์เพื่อเสนอแนวทางการจัดการการกับความกลัวและความเจ็บปวดของผู้ป่วยเด็กที่ได้รับการทำหัตถการการแทงเข็ม เริ่มจากการเตรียมความพร้อมของผู้ดูแลและตัวเด็กตั้งแต่ในระยะก่อนแทงเข็ม การดูแลในขณะที่เด็กได้รับการแทงเข็ม และการดูแลภายหลังที่เด็กได้รับการแทงเข็มโดยมีเป้าหมายเพื่อให้การพยาบาลผู้ป่วยเด็กและครอบครัวได้อย่างมีประสิทธิภาพและคุณภาพชีวิตที่ดีของเด็กป่วยและครอบครัว Managing Fear Needle Pain in Children : Nursing Practice in Pediatric care A concern is the pain-related fear of children who are about to receive needle procedures which may result in aggressive, incorporated with treatment and phobia. Fear of pain in a child is challenging for nurses regarding how to manage overcoming pain in children. Unaddressed or neglected fear of pain is often present in children, particularly in a busy clinical setting. The aim of this article was to provide the psychological techniques for early detection and practices on how to approach children with fear of pain regarding needle shots. The practices provide an effective assessment for nurses for the early detection of verbal or non-verbal symptoms. Furthermore, post procedural care is necessary to release the fear by touching, rewarding and reflecting. Art work is recommended for children to reflect their feelings and releasing their pain-related fear through drawing. Coordinating with their parents can markedly enhance the encounter of the child. Fear of pain in needle procedures is a normal phenomenon in children. Therefore, these practices would be beneficial for all health care professionals in managing the fear of pain in children.